Hubungan Reward And Punishment Dengan Motivasi Belajar Siswa Pada Sekolah Kelas V SD Negeri 098166 Kabupaten Simalungun - Dea Regina Purba; Asister Fernando Siagian; Winarto (JOURNAL SAINS STUDENT RESEARCH, 2023)
Based on research data, there is still low student learning motivation in class v state elementary school 098166 Simalungun Regency. This is caused by the lack of variety in the methods and media used by teachers so that students feel bored/watching and do not have the enthusiasm to participate in learning in the class. The main objective of this research is: "To determine the relationship between reward and punishment on student learning motivation in class V State Elementary School (SD) 098166 Simalungun Regency FY 2023". The influence of the variable (x) simultaneously on y is 0.000 < 0.05 and the t value is 34.510 > t table 4.351, so it can be concluded that the Reward and Punishment Relationship is successful in increasing student learning motivation.